1997
DOI: 10.1200/jco.1997.15.4.1309
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous transplantation for persistent/relapsed ovarian cancer: a multivariate analysis of survival for 100 consecutively treated patients.

Abstract: Before consideration of high-dose therapy for recurrent/persistent advanced ovarian cancer, patients should undergo debulking surgery or chemotherapy to achieve a minimal disease state. Patients with platinum-resistant, bulky disease should not be transplanted. The optimal patients for this therapy may be those with minimal disease responsive to initial chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
9

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 14 publications
3
55
0
9
Order By: Relevance
“…9,24 Retrospective and prospective non-randomized clinical trials of high-dose chemotherapy in epithelial ovarian cancer have confirmed high response rates and pathologic complete responses in chemotherapy-resistant patients. Furthermore, early reports of survival curves suggesting a plateau in progression-free and overall-survival at 24-48 months following treatment 6,7 have been confirmed in more recent publications of Stiff et al, 25 Legros et al 26 and Shinozuka et al 27 Prognostic factors have been examined by Stiff et al 25 They have shown that age, tumor bulk at the time of transplant, and platinum sensitivity, are predictive of longerterm survivals. Recent data from the European Intergroup (GINECO) study suggests a statistically significant median disease-free survival for patients receiving consolidation high-dose chemotherapy compared to patients receiving conventional-dose chemotherapy.…”
Section: Discussionmentioning
confidence: 70%
“…9,24 Retrospective and prospective non-randomized clinical trials of high-dose chemotherapy in epithelial ovarian cancer have confirmed high response rates and pathologic complete responses in chemotherapy-resistant patients. Furthermore, early reports of survival curves suggesting a plateau in progression-free and overall-survival at 24-48 months following treatment 6,7 have been confirmed in more recent publications of Stiff et al, 25 Legros et al 26 and Shinozuka et al 27 Prognostic factors have been examined by Stiff et al 25 They have shown that age, tumor bulk at the time of transplant, and platinum sensitivity, are predictive of longerterm survivals. Recent data from the European Intergroup (GINECO) study suggests a statistically significant median disease-free survival for patients receiving consolidation high-dose chemotherapy compared to patients receiving conventional-dose chemotherapy.…”
Section: Discussionmentioning
confidence: 70%
“…In recent studies, 1,2 treatment with high-dose chemotherapy and peripheral blood stem cell (PBSC) or bone marrow transplantation has shown promising results in selected patients. In a study by Stiff et al, 2 patients with recurrent, platinum-sensitive disease had approximately a 33% 5-year survival rate with this treatment approach. Transplantation of autologous PBSC is generally associated with more rapid hematological recovery than transplantation of bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In other tumor types such as lymphoma and sarcoma, ifosfamide has been shown to have a significant dose-response relationship. The experience with high-dose ifosfamide comes mostly from studies done in patients with soft tissue or bone sarcomas where doses of up to 14 g/m 2 with filgrastim have been used successfully without the need for PBSC support. 19 Etoposide is a glycosidic derivative of epidophyllotoxin previously shown to be associated with a dose-related cell cycle perturbation in ovarian cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cure of patients with acute leukemia [8][9][10], lymphoma [11][12][13][14][15], testicular cancer [16][17][18][19][20][21], and ovarian cancer [22][23][24][25] by transplantation strategies is predicated on achieving a complete response. Adjuvant chemotherapy for breast cancer has established that the elimination of micrometastases is achievable, even with regimens noncurative in metastatic disease [26][27][28][29][30].…”
Section: Basis For Hdc and Pbpctmentioning
confidence: 99%